School Refusal pada Anak Usia 4-5 Tahun Ditinjau dari Perkembangan Sosial - Fitroh, Siti Fadjryana; Oktavianingsih, Eka; Mayangsari, Dewi; Fa’idah, Mutimmatul (Indonesian Journal of Educational Assessment, 2019)
This study aims to perceive the social development of  children aged 4-5 years with school refusal. This research used descriptive qualitative approach. Data analysis is conducted through three stages: data reduction, display data, and conclusions: drawing/verifying. The participants of this study are 4 children aged 4-5 years. The results of this study indicated that 1) The behavior captured on school refusal in children aged  4-5 year olds consisted of refusing to go to school, having absent for several days, and having difficulties in learning or making friends. There was a difference in school refusal for boys and girls. Boys  are more dominantly having school refusal than girls. 2) The social development of children’s school refusal especially on the self-awareness aspect are: the children’s lack of confidence and they need help to understand the rules and be discipline. In the sense of responsibility to theirself and others, they need a assist to share, support and help friends. In the aspect of child’s prosocial behavior, they require a help to get along with their friends, less appreciate the friends’ work, and do not show their empathy. Furthermore, it has been found the differences of social development on school refusal children between men and women. It has been revealed that boys tend to be less independent, not confident, unfrriendly, and less appreciate their friends’ work. Moreover, girls are more independent, showing confidence, willing to play with friends, and appreciate friends’ help.AbstrakPenelitian ini bertujuan untuk mengetahui perkembangan sosial anak school refusal usia 4-5 tahun. Penelitian ini menggunakan pendekatan kualitatif metode deskriptif. Analisis data dilakukan melalui tiga tahapan: data reduction, data display, dan conclusions: drawing/verifying. Subjek dalam penelitian ini 4 anak usia 4-5 tahun. Hasil penelitian ini menunjukkan bahwa 1) Gambaran school refusal anak usia 4-5 tahun terdiri dari menolak berangkat sekolah, absen sekolah selama beberapa hari, dan kesulitan belajar atau bergaul. Ditemukan perbedaan school refusal anak laki-laki dan anak perempuan. Anak laki-laki lebih mengalami school refusal daripada anak perempuan. 2) Perkembangan sosial anak school refusal yaitu pada aspek kesadaran diri anak kurang percaya diri dan membutuhkan bantuan untuk memahami peraturan dan disiplin. Pada aspek rasa tanggung jawab terhadap diri sendiri dan orang lain membutuhkan bantuan untuk berbagi, menolong dan membantu teman. Pada aspek perilaku prososial anak membutuhkan bantuan untuk bergaul dengan teman, kurang menghargai karya teman, dan tidak menunjukkan empati. Ditemukan perbedaan perkembangan sosial anak school refusal antara laki-laki dan perempuan. Terlihat anak laki-laki cenderung kurang mandiri, tidak percaya diri, menyendiri, dan kurang menghargai teman. Anak perempuan lebih mandiri, menunjukkan percaya diri, mau bermain bersama teman, dan mau menghargai teman dengan bantuan.